Linguistic Geography of Nepalese Languages - Khanal, Rajendra (The Third Pole: Journal of Geography Education, 2019)
The main aim of this paper is to present the linguistic geography of Nepalese languages with a brief introduction to linguistic geography using secondary sources of data. The study is focused to identify and analyze the diversity within a language. Different tables are prepared to determine a common ground in geographical bases to study language in geographical, social, cultural and historical relativity. A wide range of diversities found in major languages that spoken in Nepal i.e. Newar, Magar, Rai, Tharu and Nepali. The findings indicate that linguistic variables are formed out of the geographical diversity. All languages of Nepal have their own geography and cultural background.